Effects of spin density wave quantization on the electrical transport in epitaxial Cr thin films - Osquiguil, E.; Kaul, E.E.; Tosi, L.; Balseiro, C.A. (American Physical Society, 2012)
Fil: Osquiguil, E. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina